2014
DOI: 10.1128/aem.02817-13
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment of Glyco- and Phospholipid Separation by Using Silica Chromatography

Abstract: Phospholipid-derived fatty acids (PLFAs) are commonly used to characterize microbial communities in situ and the phylogenetic positions of newly isolated microorganisms. PLFAs are obtained through separation of phospholipids from glycolipids and neutral lipids using silica column chromatography. We evaluated the performance of this separation method for the first time using direct detection of intact polar lipids (IPLs) with high-performance liquid chromatography-mass spectrometry (HPLC-MS). We show that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…However, it has been shown that the phospholipid fraction also contains other non-P containing intact polar lipids (Heinzelmann et al, 2014). The glycolipid- and phospholipid fractions were therefore combined and are further referred to as structural, membrane-derived lipids.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been shown that the phospholipid fraction also contains other non-P containing intact polar lipids (Heinzelmann et al, 2014). The glycolipid- and phospholipid fractions were therefore combined and are further referred to as structural, membrane-derived lipids.…”
Section: Methodsmentioning
confidence: 99%
“…E,F). A recent study by Heinzelmann et al () shows that the separation of glycolipids from phospholipids by commonly used silicate column chromatography is incomplete, and that glyco‐ and other lipids also elute in the methanol fraction. However, both glyco‐ and phospholipids are structural (membrane) lipids in contrast to the neutral storage lipids in the chloroform fraction, and therefore, the data for these two membrane fractions was combined in this study.…”
Section: Assessmentmentioning
confidence: 99%
“…Normal-phase SPE fractionation of lipids has been applied for many years [21]. However, potential issues in selectivity with silica-based SPE fractionation of plant lipids have been shown [22]. The selectivity using half the solvent elution volumes was compared using an LC-MS method previously described [23].…”
Section: Resultsmentioning
confidence: 99%